The Role of the Consumer Protection Law on the Development of Information Technology for MSMEs in Indonesia - Hasdiana Juwita Bintang; Lidya Rahmadani Hsb; Altika Mustikasyari (Yayasan Multidimensi Kreatif, 2024)
This study aims to describe technological developments in MSME activities in Indonesia which are supervised by the Consumer Protection Law (Law Number 8 Than 1999). The research method used is descriptive with the type of normative research, the data collection method is carried out by literature study, the analysis used is qualitative analysis. The brief description in the study is that the development of the national economy is supported by the development of information technology through the growth of the digital economy and electronic information by utilizing information technology and electronic transactions. Legal protection is intended as protection provided by the state to every citizen whose rights are harmed. Legal protection is the foundation of a just legal system and can create a framework for resolving conflicts, defending individual rights and maintaining social order. It is important to ensure that the government and authorities cannot act arbitrarily against citizens.